Analysis of 10-Year Training Results of Medical Students Using the Microvascular Research Center Training Program - Onoda, Satoshi; Kimata, Yoshihiro; Sugiyama, Narushi; Tokuyama, Eijiro; Matsumoto, Kumiko; Ota, Tomoyuki; Thuzar, Moe (Journal of Reconstructive Microsurgery, 2016)
Background In this article, we reviewed the training results of medical students using the Microvascular Research Center Training Program (MRCP), and proposed an ideal microsurgical training program for all individuals by analyzing the training results of medical students who did not have any surgical experience.Methods As of 2015, a total of 29 medical students completed the MRCP. In the most recent 12 medical students, the number of trials performed for each training stage and the number of rats needed to complete the training were recorded. Additionally, we measured the operating time upon finishing stage 5 for the recent six medical students after it became a current program.Results The average operating time upon finishing stage 5 for the recent six medical students was 120 minutes ± 11 minutes (standard deviation [SD]). The average vascular anastomosis time (for the artery and vein) was 52 minutes ± 2 minutes (SD). For the most recent 12 medical students, there was a negative correlation between the number of trials performed in the non-rat stages (stages 1–3) and the number of rats used in the rat stages (stages 4–5).Conclusion Analysis of the training results of medical students suggests that performing microsurgery first on silicon tubes and chicken wings saves animals' lives later during the training program. We believe that any person can learn the technique of microsurgery by performing 7 to 8 hours of training per day over a period of 15 days within this program setting.
Keywords: microsurgery; training program; medical student